OPTIMALISASI PERAN PEMERINTAH DAERAH DI BIDANG PELAYANAN KESEHATAN BERDASARKAN ASAS RESPONSIBILITAS - I Gusti Ayu Eviani Yuliantari (Jurnal Hukum Mimbar Justitia, 2023)
Regional Government is one of the elements of government that supports the implementation of regional government. To run regional government, it is carried out by optimizing the role of regional government, especially in the implementation of government affairs, both absolute government affairs, concurrent government affairs and mandatory government affairs. One of the government affairs in this article is related to health services which are part of concurrent government affairs. Concurrent government affairs are regional government affairs which are carried out based on the principle of regional autonomy by prioritizing the principles of decentralization, deconcentration and assistance tasks. It should be noted that in implementing regional autonomy, regional governments are obliged to prioritize services using the principles of good governance. In this case, the author is interested in discussing What are the legal regulations regarding health services as part of regional government affairs? And how to optimize the role of local government in the field of health services by prioritizing the principle of responsibility? Because as is known, based on the principle of responsibility, the government must comply with laws and regulations and carry out responsibilities towards society and the environment so that it can run well and the government can be managed well and correctly. In this research, the author uses a legal concept approach and a statutory regulations approach which will examine how regional governments implement the principle of responsibility in accordance with the provisions of statutory regulations and also regional policies based on the principle of regional autonomy.Keywords: Good Governance; Regional autonomy; Responsibility.